Phenotypic differences in teeth dimensions among Chennai population: An aid in sex determination - Sreedevi Dharman; N Gnanasundaram; Maragathavalli Gopal; Arvind Muthukrishnan (Wolters Kluwer Medknow Publications, 2015)
Objective: To investigate the presence of sexual dimorphism by studying the size of the teeth among males and females in Chennai population, which aids in sex determination. Materials and Methods: Incisocervical length, mesiodistal and buccolingual diameters were measured in teeth of 60 subjects (30 males, 30 females) in the age group of 18-22 years from Chennai population. The differences in the mean values of parameters in males and females were calculated using independent t-test. Discriminant functional analysis was performed to determine the accuracy of sex. Results: Significant differences were found in mean incisocervical length which were found to be larger in males with P < 0.05 in 11, 12, 14, 17, 21, 22, 24, 26, 27, 31, 32, 33, 34, 41, 43, and 45 and with P < 0.001 in 13, 23, 32, 42, 43, and 44, with the exception of 37 and 47 which were larger in females. Mean mesiodistal diameter was larger in males with P < 0.05 in 11, 12, and 21 and with P < 0.001 in 13, 23, 33, and 43. Mean buccolingual diameter was larger in males with P < 0.05 in 12, 21, 31, 33, and 41 and with P < 0.001 in 11, 13, 23, and 43. Accuracy rate of predicting sex based on incisocervical length (17, 23, 47) and mesiodistal diameter (13, 33) was 78.3% and based on buccolingual diameter (13) was 76.7%. Conclusion: Males showed greater sexual dimorphism than females. Application of incisocervical, mesiodistal, and buccolingual dimensional variability among males and females in the Chennai population can aid in sex determination in forensic odontology, as the results showed moderate extent of dimorphism with an overall accuracy rate of predicting sex to be 78%.